THE CONSTITUTION OF THE REPUBLIC OF UZBEKISTAN IS A GUARANTEE OF THE IMPLEMENTATION OF LABOR RIGHTS - Burkhankhodjaeva Khurshida Vakhdatovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The whole world, including Uzbekistan, is currently facing a difficult situation in the field of labor relations in the context of a pandemic. This requires a revision of existing labor legislation, and in some respects the introduction of new rules on a theoretical basis. It is necessary to protect the constitutional rights of people to work in the context of a pandemic, to provide them with a minimum wage for their work in the country, to strengthen their social protection.